Psychological aspects of adolescents’ tolerant attitude to children with special educational needs in terms of joint learning (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the problem of development oftolerance in adolescent pupil environment to children with specialeducational needs as participants of the educational process.Theinstability of the processes of personality formation of adolescents andtheir unreadinessto adequately communicate with such children areemphasized.The results of an empirical research aimed at studyingthereadiness to promote interaction with classmates who have specialeducational needs are presented. The level of tolerance formation amongadolescents is determined.
Keywords: : tolerance, children with special educational needs, pupil environment, inclusion, adolescence, educational process